ANALISIS KESALAHAN PENGGUNAAN AFIKS PADA KARANGAN NARASI SISWA KELAS VII-A SMP NEGERI 2 TOMA - Sinaria Laia (Universitas Nias Raya, 2026)
The problem highlighted in this study is that students' use of affixes in narrative essays does not fully conform to Indonesian language rules. The aim of this research is to analyze errors in affix usage in the narrative essays of Grade VII-A students at SMP Negeri 2 Toma. This study uses a quantitative descriptive approach, with student narrative essays serving as the data source. The results indicate that errors in affix usage occur with the prefixes meN-, ber-, di-, peN-, and se-, with the most frequent error being the misuse of the prefix di-. This issue stems from the influence of the native language or local dialect and insufficient writing skills to grasp the nuances of writing tasks. The researcher recommends: (1) Teachers should effectively instruct students on proper Indonesian language usage according to established guidelines and enhance vocabulary while providing clear examples of correct usage both orally and in writing to motivate students. (2) Students should focus on expanding their vocabulary to produce accurate and well-written texts. To improve their understanding of affixation, they should read various sources, including books and online materials, to use as references. Reading both fiction and non-fiction can help clarify word usage and frequent reading can enhance their ability to express ideas in writing. (3) Schools should ensure access to a range of reading materials, such as resources on writing skills, EYD (Enhanced Spelling System), KBBI (Indonesian Dictionary), and both fiction and non-fiction texts, to serve as references for broadening knowledge and improving writing skills.